Compensation assessment practices in expropriation of customary land rights in Malawi - Kabanga, Lucky (Department of Construction Economics and Management, 2022)
Providing various public infrastructure requires a lot of land that is normally expropriated from private and/or customary owners as government may not have it, in return for compensation to cover the expropriatory losses occasioned. Commonly, such compensation is assessed based on market value. While private land is tradable, customary land is conceptually and statutorily not. Essentially, the study examines how expropriated customary land is valued for compensation purposes. It argues that existing compensation valuation practices for expropriation presupposes private property and functional property markets, thereby realising inadequate compensation for customary land. By doing so, the study analyses applicability of indemnity and taker's gain compensation theories and methodologies that are founded on private land, to customary properties and in different social settings, to achieve desired compensation goals. The study uses three case studies in Malawi to collect empirical data through face-to-face interviews and focus group discussions from sixty respondents that included key informants, expropriatees, government officials, government valuers, private valuers, local leaders, development partner and civil society organisations representatives. Qualitative data were analysed qualitatively through thematic analysis and simple descriptive analysis for quantitative data. The study finds that Malawian compensation law derives from indemnity compensation theory but that its applicability to customary land is challenged by various factors including inadequate and unsupportive laws, underdeveloped or non-existent land markets to support adopted market value-based methodologies, customary land prevalence, absence of assessment methodologies for non-tradable or rarely exchanged properties and noncompensation of various expropriatory losses. The study concludes that indemnity compensation is fundamentally applicable to customary land as it desires to protect land rights from arbitrary takings and prevent expropriatees from impoverishment, but that current compensation practices obtain inadequate compensation that impoverishes expropriatees. This calls for other non-market dependent compensation assessment methodologies such as Contingent Valuation Methodology. The study makes a contribution to knowledge regarding the compensation of customary land acquired compulsorily, in the areas of theory, empirical data and policy development.